Pengaruh Eco-Friendly Practices, Green Image, Dan Brand Attachment Terhadap Brand Advocacy Dan Brand Loyalty Generasi Z Pada Industri Coffee Shop - Miftahul Jannah; Wijanarko, Faiq; Rahayu, Fatik (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2025)
This study explores the impact of Eco-Friendly Practices (EFP) implementation in Indonesian coffee shops on green image, brand attachment, brand advocacy, and brand loyalty among Generation Z. Using a quantitative approach, data were collected through a survey of 110 Generation Z respondents visiting environmentally friendly coffee shops. The findings reveal that EFP significantly influences green image and brand attachment. Furthermore, brand attachment positively affects brand advocacy and loyalty. These results emphasize the importance of EFP as a sustainable business strategy that not only supports environmental preservation but also strengthens consumers' emotional connection and loyalty to the brand. This research is expected to serve as a reference for café owners in formulating environmentally friendly business strategies to attract younger consumers.